2007
DOI: 10.1186/1471-2148-7-58
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of Cucumis (Cucurbitaceae): Cucumber (C. sativus) belongs in an Asian/Australian clade far from melon (C. melo)

Abstract: BackgroundMelon, Cucumis melo, and cucumber, C. sativus, are among the most widely cultivated crops worldwide. Cucumis, as traditionally conceived, is geographically centered in Africa, with C. sativus and C. hystrix thought to be the only Cucumis species in Asia. This taxonomy forms the basis for all ongoing Cucumis breeding and genomics efforts. We tested relationships among Cucumis and related genera based on DNA sequences from chloroplast gene, intron, and spacer regions (rbcL, matK, rpl20-rps12, trnL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 30 publications
4
101
0
1
Order By: Relevance
“…With regard to differences among reference accessions, which are from various cultivar groups and species of Cucumis, the genetic variability observed among Iranian accessions is significantly comparable with reference accessions. These results demonstrate that the Iranian melon is diversified and supports the idea of their origin in Asia (Renner et al 2007). In addition, it indicates the importance of Iranian inodorus and dudaim accessions for the study of origin and diversification of vars.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…With regard to differences among reference accessions, which are from various cultivar groups and species of Cucumis, the genetic variability observed among Iranian accessions is significantly comparable with reference accessions. These results demonstrate that the Iranian melon is diversified and supports the idea of their origin in Asia (Renner et al 2007). In addition, it indicates the importance of Iranian inodorus and dudaim accessions for the study of origin and diversification of vars.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, 'Musk' is a Persian word for a kind of perfume and 'melon' is derived from Greek words (Robinson and Decker-Walters 1997). The origin of diversity for melon was traditionally believed to be in Africa (Robinson and Decker-Walters 1997), although recent molecular systematic studies, suggested that it may be originated from Asia and then reached to Africa (Renner et al 2007). Central Asia, Iran, Afghanistan, India, Transcaucasia, Turkmenistan, Tajikistan, and Uzbekistan, as well as Afghanistan and China (Robinson and DeckerWalters 1997) are considered primary diversity centre for melon (Tzitzikas et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The protein sequence is largely conserved among cucurbital taxonomic group, but not in other Eudicotyledons, indicating that APRX might be a Cucurbitaceae speciWc peroxidase. Cucumis organellar genomes are unusually labile and numerous accumulations of repetitive sequences as well as major rearrangements are thought to have taken place during the evolution of Cucumis (Renner et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies test whether this holds true for their dataset although it is known that the outcome of bootstrap analyses may be highly dataset dependent (DeBry and Olmstead, 2000;Mort et al, 2000;Sanderson and Wojciechowski, 2000). Further, Müller's (2005b) conclusions have been extrapolated for use under RAS too (Renner et al, 2007;Komarova et al, 2008). To test the possible influence of RAS versus simple addition sequence and few versus many bootstrap iterations on the present dataset we ran four separate bootstrap analyses with full heuristic searches, holding one tree per taxon addition sequence, with TBR branch swapping: (1) RAS-500:500 bootstrap replicates, each of 50 replicates of RAS, saving no more than 10 trees in each replicate; (2) RAS-10,000:10,000 bootstrap replicates, each of 1 replicate of RAS, saving no more than one tree per replicate; (3) SIMPLE-500:500 bootstrap replicates, simple addition sequence, holding up to 50 trees during TBR branch swapping; (4) SIMPLE-10,000:10,000 bootstrap replicates, simple addition sequence, holding up to 50 trees during TBR branch swapping.…”
Section: Parsimony Analyses and Monophyly Testingmentioning
confidence: 99%